Deriving the Cartography of the Japanese Right Periphery: The Case of Sentence-Final Discourse Particles - Saito, Mamoru; Haraguchi, Tomoko (IBERIA: An International Journal of Theoretical Linguistics, 2014)
The cartographic structure of the Japanese right periphery has been investigated extensively over recent years. (See, for example, Inoue 2007, Ueda 2007, Saito 2009, Endo 2010, and the references cited there.) This paper examines the distributions of the sentence-final discourse particles and presents an account in terms of their lexical properties. We argue, following Endo (2010), that the particles, wa, yo, ne and na, indeed instantiate a cartographic structure in the right periphery. Then, we examine the lexical properties of each of those particles, and show that they explain the observed hierarchy. More specifically, we argue that the selectional requirement of wa and the specific speech acts the four particles are associated with yield the hierarchy wa < yo < ne/na. This conclusion implies that the cartographic structure of the Japanese sentence-final discourse particles can be considered a consequence of the Merge operation that reflects the lexical properties of those particles.